Thirteen years of sharka disease in Valencia, Spain - Llácer, Gerardo; Cambra, Mariano (2017)
Since the initial detection of PPV in Valencia (Spain), work on improvement of diagnosis methods and virus characterization have been developed, mainly with serological methods. Comparison of traps and sampling methods to evaluate aphid populations in the orchards, as well as identification of potential vectors have been made. Epidemiology and analysis of the spatial spread of PPV has also been accomplished. A breeding program was started in 1993 and its aim was to obtain apricot varieties resistant to PPV and well adapted to our conditions. Finally, in 1996, we have initiated the evaluation of the resistance of transgenic plums expressing PPV coat protein gene, as well as the risks from using these plants in the fields.